Measuring well-being in emerging adults: Exploring the PERMA framework for positive youth development - Leontopoulou, Sophie (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The PERMA theory brings together elements of the PERMA model, character strengths, and well-being. Set in the context of positive education this study set out to empirically test this multidimensional theory with emerging adults in higher education. 516 female and male students aged 18 to 29 years studying in Universities in Greece were asked to participate in a web-based survey of (a) the five elements of PERMA, i.e. positive emotions, engagement, relationships, meaning and accomplishment; (b) four character strengths, i.e. curiosity, gratitude, love for learning and humor; and (c) three well-being indicators, i.e. flourishing, resilience and positive perception. The patterning of associations within and between the three components of the theory was examined, leading to insights regarding both the multidimensionality of well-being and the specificity of relations between the three components. Conclusions were drawn regarding the theoretical and applied implications of the results for advancing positive youth development in higher education.